MINI REVIEW: PENGARUH PERENDAMAN TELUR MENGGUNAKAN ESTRAK DAUN SEREH WANGI (CYMBOPOGON NARDUS L.) TERHADAP KUALITAS INTERNAL DAN DAYA AWET TELUR AYAM RAS - Sedya, Iga Wahyuning; Rinawidiastuti, Rinawidiastuti (Jurnal Peternakan Nusantara, 2022)
Eggs are livestock products that are easily contaminated by microbes either directly or indirectly with pollutants from soil, air, water and dust. Eggs if stored at room temperature only last 10-14 days, after that time the eggs undergo changes such as evaporation of water content through the pores of the egg shell which results in a decrease in egg weight, changes in chemical composition and the occurrence of dilution of egg contents. One of the efforts to extend the shelf life of eggs is to provide soaking treatment using citronella leaf extract. Citronella leaves are one of the plants that contain tannins. The most specific characteristic of citronella is antioxidants so that it can be used as a natural preservative to replace synthetic preservatives, because lemongrass contains active components such as geraniol and citranelol, these active components can play an active role so that citronella can be used as a natural preservative. This review aims to provide information and results of research that has been carried out using citronella leaf extract as a natural preservative for eggs by immersion treatment. The author reviews this article by conducting a literature study. The paper was obtained from Rani et al, (2021), the journal is a national journal. The literature was obtained from the online journal site google scholar with the keywords "eggs", "citronella extract", and "soaking". The addition of citronella leaf extract with different concentrations of 10, 20 and 30% and soaking time for 6, 12, and 24 hours. Soaking eggs using citronella leaf extract has a significant effect on the durability of eggs. Keywords: eggs, citronella extract, soaking